2022
DOI: 10.46634/riics.131
|View full text |Cite
|
Sign up to set email alerts
|

Productivity costs associated to voice symptoms, low sleep quality, and stress among college professors during homeworking in times of COVID-19 Pandemic

Abstract: Objective. To estimate the productivity reduction costs associated to self-reported voice symptoms, low sleep quality, and high stress levels among college professors during homeworking in times of COVID-19 pandemic. Methods. This cross-sectional study included fifty-eight college professors who reported their reduction in productivity at work due to self-perceived stress levels, sleep quality, and voice symptoms. Results. High stress levels were reported by 24% of the participants, whereas 19% reported voice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A recent study reported that teachers who raised their vocal loudness during online teaching experienced significantly higher-stress levels ( 16 ) . In addition, productivity reduction costs in teachers associated with high stress levels were around US$8,210 during pandemic COVID-19 ( 17 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that teachers who raised their vocal loudness during online teaching experienced significantly higher-stress levels ( 16 ) . In addition, productivity reduction costs in teachers associated with high stress levels were around US$8,210 during pandemic COVID-19 ( 17 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been highlighted the importance of implementing workplace vocal and mental health programs in educational settings to reduce the occurrence of voice disorders and stress levels among teachers ( 13 , 17 ) . However, there is a lack of studies that report workplace programs to improve teachers’ quality of life and voice functioning ( 18 ) .…”
Section: Introductionmentioning
confidence: 99%